2020
DOI: 10.1002/job.2426
|View full text |Cite
|
Sign up to set email alerts
|

Audience perceptions of high‐status ties and network advantage: The market for coaching jobs in the National Collegiate Athletic Association (2000–2011)

Abstract: Social ties with high-status others can be a potent signal of an individual's underlying quality and future promise. Individuals in competitive markets, therefore, have an incentive to publicly claim connections to high-status others. However, cognitive limitations and biases can make social network connections difficult for observers to reliably discern, and claims to high-status ties can go unrecognized by the audience.Our core contention is that claims to high-status affiliation are advantageous only when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Extant research on social capital have offered evidence for the direct effect of government social capital on firms’ innovation (Chen et al , 2021; Zhang et al , 2019; Jean et al , 2018; Wang et al , 2022), with inadequate attention has been paid to the internal mechanisms (Li et al , 2018). Although quite few previous studies have examined the mediating effect of institutional support (Zhang et al , 2019) and knowledge exchange (Shu et al , 2012) in the relationship between firm’s government social capital and firm innovation, they mainly pay attention to the resources and information gained through connecting with government (Wang et al , 2022; Halgin et al , 2020), which ignores the role of having social ties with government in signaling firms’ quality and legitimacy promoting others’ evaluation toward the focal firm in the network (i.e. network prestige; Podolny, 2001; Baum and Oliver, 1992; Halgin et al , 2020) especially for firms in emerging economies (Arnoldi and Villadsen, 2015; Dieleman and Boddewyn, 2012; Kostka and Zhou, 2013; Peng and Luo, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant research on social capital have offered evidence for the direct effect of government social capital on firms’ innovation (Chen et al , 2021; Zhang et al , 2019; Jean et al , 2018; Wang et al , 2022), with inadequate attention has been paid to the internal mechanisms (Li et al , 2018). Although quite few previous studies have examined the mediating effect of institutional support (Zhang et al , 2019) and knowledge exchange (Shu et al , 2012) in the relationship between firm’s government social capital and firm innovation, they mainly pay attention to the resources and information gained through connecting with government (Wang et al , 2022; Halgin et al , 2020), which ignores the role of having social ties with government in signaling firms’ quality and legitimacy promoting others’ evaluation toward the focal firm in the network (i.e. network prestige; Podolny, 2001; Baum and Oliver, 1992; Halgin et al , 2020) especially for firms in emerging economies (Arnoldi and Villadsen, 2015; Dieleman and Boddewyn, 2012; Kostka and Zhou, 2013; Peng and Luo, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Up to present, few studies have investigated the role played by institutional support from the government (Zhang et al , 2019), knowledge exchange with government and business partners (Shu et al , 2012) and the formation of business ties (Zhang et al , 2020) in the relationship between firm’s government social capital and firm innovation. The existing studies focused mainly on the information and resources gained through connecting with the government (Wang et al , 2022; Halgin et al , 2020). We argue that social networks are not only beneficial to the access to the information and resources as “pipes,” but they also act as “prisms” that signal the legitimacy and quality products of firms through having social ties with prominent institutions, and then promote others’ evaluation toward them (Podolny, 2001; Baum and Oliver, 1992; Halgin et al , 2020) in the industry network (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of this contrasting perspective is that the resources networks provide accumulate rather than dissipate over time. It is also possible that the conditions that prevail at the time of network formation leave a lasting, “imprinted” effect that shapes outcomes for the actor long afterwards (e.g., Halgin et al, 2020). Networks that are formed during a formative period in an individual's (or organization's) development may be particularly conducive to learning (McEvily et al, 2012) and may therefore have a lasting effect on individual performance.…”
Section: Phase II Challenges and Prospects For Future Researchmentioning
confidence: 99%
“…In the context of Nashville's legal industry, McEvily et al (2012) found that bridging ties produced network benefits over an extended period of time and could be traced back to the point of tie formation. In the context of the market for head coaches in NCAA basketball, Halgin, Borgatti, Mehra, and Soltis (2020) found that ties to star head coaches forged early in a coach's career were more likely to be recognized by others and allowed coaches to outperform their peers in the market for coaching jobs.…”
Section: Performancementioning
confidence: 99%